2013
DOI: 10.4103/1119-3077.110164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of IVF/ICSI outcome in patients with polycystic ovarian syndrome or tubal factor infertility

Abstract: IVF/ICSI performance in patients with PCOS is probably similar to their counterparts with tubal factor infertility with, however, a reduced fertilization rate and higher incidence of OHSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 26 publications
1
28
1
Order By: Relevance
“…PCOS women had slightly lower fertilization rate in IVF cycles, but signi icantly higher fertilization rate in ICSI cycles indicating that there were certain abnormalities in zona pellucida of PCOS patients that resulted in decreased fertilization rate, ICSI could avert these abnormalities and thus increase fertilization rate (Gardner et al, 2018), in this study PCOS group had higher 2PN oocytes than the control group , this can be due to the use of ICSI in all women and the higher number of mature oocytes retrieved. This result disagrees with (Yin et al, 2015) and (Kahyaoglu et al, 2015) where fertilization rate did not show a statistically different rate between PCOS and control group and not agree with other studies (Zhong et al, 2012;Okohue et al, 2013;Rehman et al, 2018) which explain the lower fertilization rate in PCOS group by the asso- In the current study no difference is found between PCOS women and controls regarding the number of grade 1 embryo, this result is similar to (Kahyaoglu et al, 2015) , however other study (Zhong et al, 2012) showed a lower number of grade 1 embryo attributed to endocrine abnormalities associated with PCOS and internal oocytes abnormalities both signi icantly reduce the quality of the developing embryo. The present study demonstrates similar biochemical and clinical pregnancy rates between the PCOS group and control group.…”
Section: Resultscontrasting
confidence: 82%
See 1 more Smart Citation
“…PCOS women had slightly lower fertilization rate in IVF cycles, but signi icantly higher fertilization rate in ICSI cycles indicating that there were certain abnormalities in zona pellucida of PCOS patients that resulted in decreased fertilization rate, ICSI could avert these abnormalities and thus increase fertilization rate (Gardner et al, 2018), in this study PCOS group had higher 2PN oocytes than the control group , this can be due to the use of ICSI in all women and the higher number of mature oocytes retrieved. This result disagrees with (Yin et al, 2015) and (Kahyaoglu et al, 2015) where fertilization rate did not show a statistically different rate between PCOS and control group and not agree with other studies (Zhong et al, 2012;Okohue et al, 2013;Rehman et al, 2018) which explain the lower fertilization rate in PCOS group by the asso- In the current study no difference is found between PCOS women and controls regarding the number of grade 1 embryo, this result is similar to (Kahyaoglu et al, 2015) , however other study (Zhong et al, 2012) showed a lower number of grade 1 embryo attributed to endocrine abnormalities associated with PCOS and internal oocytes abnormalities both signi icantly reduce the quality of the developing embryo. The present study demonstrates similar biochemical and clinical pregnancy rates between the PCOS group and control group.…”
Section: Resultscontrasting
confidence: 82%
“…In spite of high E2 levels on the hCG trigger day, number of follicles, number of retrieved oocytes and mature oocytes, fertilization (2PN oocytes) were signi icantly higher in the PCOS group in comparison to control group, this same result was observed in the previous stud-ies. (Zhong et al, 2012;Yin et al, 2015;Okohue et al, 2013;Rehman et al, 2018;Zhang et al, 2013). The result of this study demonstrated that the measured FF and serum G-CSF concentrations on the day of oocyte retrieval were signi icantly higher in patients with PCOS undergoing IVF treatment in comparison to control group, while there was no statistical difference between these two groups regarding FF and serum IL15.…”
Section: Resultsmentioning
confidence: 51%
“…PCOS women with reproductive problems searching arti cial insemination with intracytoplasmic sperm injection (ICSI) showed no signi cant difference in serum fetuin-A levels, as compared to ICSI-treated non-PCOS ones [68]. However, fetuin-A level in follicular uid of non-PCOS women was signi cantly higher than that in the follicular uid of women with PCOS.…”
Section: © Medical University Plevenmentioning
confidence: 97%
“…Selection of study group scored highly amongst the included studies; all studies scored at least three out of four stars. On assessment of comparability (confounding), only 10 studies (Urman et al, 1992;Homburg et al, 1993;Sengoku et al, 1997;Palep-Singh et al, 2007;Mellembakken et al, 2011;Kalra et al, 2013;Okohue et al, 2013;Li et al, 2014;Almasi-Hashiani et al, 2018) matched or adjusted for age between the two compared groups, and only two (Li et al, 2014;Almasi-Hashiani et al, 2018) adjusted or matched for BMI. A further five studies were awarded a star for similar age (Doldi et al, 1999;Weghofer et al, 2007;Tehrani Nejad et al, 2011;Chen et al, 2016;Shi et al, 2018;Hwang et al, 2016), and one study awarded a star for equivalent BMI (Melado Vidales et al, 2017).…”
Section: Assessment Of Biasmentioning
confidence: 99%